miRNAs in Tuberculosis: New Avenues for Diagnosis and Host-Directed Therapy - Sabir, Naveed; Hussain, Tariq; Shah, Syed Zahid Ali; Peramo, Antonio; Zhao, Deming; Zhou, Xiangmei (Frontiers in Microbiology, 2018)
Tuberculosis (TB) is one of the most fatal infectious diseases and a leading cause of mortality, with 95% of these deaths occurring in developing countries. The causative agent, Mycobacterium tuberculosis (Mtb), has a well-established ability to circumvent the host’s immune system for its intracellular survival. microRNAs (miRNAs) are small, non-coding RNAs having an important function at the post-transcriptional level and are involved in shaping immunity by regulating the repertoire of genes expressed in immune cells. It has been established in recent studies that the innate immune response against TB is significantly regulated by miRNAs. Moreover, differential expression of miRNA in Mtb infection can reflect the disease progression and may help distinguish between active and latent TB infection (LTBI). These findings encouraged the application of miRNAs as potential biomarkers. Similarly, active participation of miRNAs in modulation of autophagy and apoptosis responses against Mtb opens an exciting avenue for the exploitation of miRNAs as host directed therapy (HDT) against TB. Nanoparticles mediated delivery of miRNAs to treat various diseases has been reported and this technology has a great potential to be used in TB. In reality, this exploitation of miRNAs as biomarkers and in HDT is still in its infancy stage, and more studies using animal models mimicking human TB are advocated to assess the role of miRNAs as biomarkers and therapeutic targets. In this review, we attempt to summarize the recent advancements in the role of miRNAs in TB as immune modulator, miRNAs’ capability to distinguish between active and latent TB and, finally, usage of miRNAs as therapeutic targets against TB.